The 1998 Banyuwangi Humanitarian Case (In Socio-Economic Studies) - Kayan Swastika; Robit Nurul Jamil (Budapest International Research and Critics University, 2022)
The change of power from the New Order era to the reform era was accompanied by various major problems, such as the problem of KKN (corruption, collusion, nepotism), the economic crisis, and cases of violence. One of the violence that occurred before the collapse of the New Order was the case of violence over the issue of witchcraft in Banyuwangi in 1998. Hundreds of people who were accused of being witch doctors had to die with unnatural deaths, such as; sharp weapon slashes and burns. The perpetrators are suspected to be not just anyone. This is because his features are like that of a ninja, dressed in all black, his face covered with cloth and leaving only a pair of eyes without a cover. The casualty toll exploded in August and September 1998 with 75 victims. This Writing Method uses descriptive method, which is a method that aims to describe or provide an overview of the object under study through data or samples that have been collected as they are without analyzing and making conclusions that apply to the public. Discussion, a) Social Studies, b) Human Rights and Case Studies (2017) c) Economic Studies. Conclusion. 1. The violation of Human Rights in the Massacre of Shaman Santet in Banyuwangi Regency in 1998 was a diversion of issues by the central government. 2. Violation of Human Rights in the Massacre of Shaman Santet in Banyuwangi Regency in 1998 could be a scenario carried out by the Old Order government. 3. Violation of Human Rights in the Massacre of Shaman Santet in Banyuwangi Regency in 1998 was the impact of the Monetary crisis. 4. Violation of Human Rights in the Massacre of Shaman Santet in Banyuwangi Regency in 1998 is one of the many cases of human rights violations in Indonesia that have not been or have not been resolved.